PROBLEMS OF APPLICATION OF SOME TYPES OF ALTERNATIVE CRIMINAL PENALTIES - Alisherova Nozima Nizamidin qizi (Scholar Express Journals, 2024)
In this article, the author, from a scientific and practical perspective, examines some types of alternative punishments, which are one of the most important means of the process of resocialization and correction of criminals in Uzbekistan. In particular, the article notes that these types of punishments show their positive sides today; at the same time, the fact is pointed out that some serious gaps and shortcomings in the legislation in practice have a negative impact on the effectiveness of punishments; corresponding proposals and recommendations are also presented.
Keywords: non-custodial punishment; probation; fine; correctional labor